THE CASE FOR ARCHAEAN BONINITES - Smithies H.R.; Champion D.C.; Sun S.-S. (My University, 2004)
Rare Archaean light rare earth element (LREE)-enriched mafic rocks derived from a strongly refractory mantle source show a range of features in common with modern boninites. These Archaean second-stage melts are divided into at least two distinct groups—Whundo-type and Whitney-type. Whundo-type rocks are most like modern boninites in terms of their composition and association with tholeiitic to calc-alkaline mafic to intermediate volcanics. Small compositional differences compared to modern boninites, including higher Al2O3 and heavy REE (HREE), probably reflect secular changes in mantle temperatures and a more garnet-rich residual source. Whundo-type rocks are known from 3.12 and 2.8Ga assemblages and are true Archaean analogues of modern boninites. Whitney-type rocks occur throughout the Archaean, as far back as ca. 3.8Ga, and are closely associated with ultramafic magmatism including komatiites, in an affiliation unlike that of modern subduction zones. They are characterised by very high Al2O3 and HREE concentrations, and their extremely depleted compositions require a source which at some stage was more garnet-rich than the source for either modern boninites or Whundo-type second-stage melts. Low La/Yb and La/Gd ratios compared to Whundo-type rocks and modern boninites either reflect very weak subduction-related metasomatism of the mantle source or very limited crustal assimilation by a refractory-mantle derived melt. Regardless, the petrogenesis of the Whitney-type rocks appears either directly or indirectly related to plume magmatism. If Whitney-type rocks have a boninitic petrogenesis then a plume related model similar to that proposed for the modern Tongan high-Ca boninites might apply, but with uniquely Archaean source compositions and source enrichment processes. Second-stage melts from Barberton (S. Africa –3.5Ga) and ca. 3.0Ga rocks from the central Pilbara (Australia) have features in common with both Whundo- and Whitney-types, but appear more closely related to the Whitney-type. Subduction zone processes essentially the same as those that produce modern boninites have operated since at least ~3.12Ga, while a uniquely Archaean boninite-forming process, involving more buoyant oceanic plates and very inefficient mantle-source enrichment, may have occurred before then.
Keywords: Precambrian::Archean; Докембрий::Архей